2020
DOI: 10.1111/jofo.12339
|View full text |Cite
|
Sign up to set email alerts
|

Self‐referent phenotype matching is a poor predictor of egg rejection by American Robins

Abstract: Many hosts of obligate brood‐parasitic birds use variation in the coloration and pattern of eggshells to identify and reject foreign eggs from their nests. However, egg‐rejection behavior of several hosts is not tightly predicted by the modeled output of overall avian‐perceivable chromatic differences between foreign and host eggs. This demands a re‐investigation into the proximate sensory cues and perceptual processes used for egg recognition. One plausible mechanism is that rejection by hosts depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 44 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…All models were painted a robin-like blue colour (paint-mix details sourced from [ 31 ]), in triplicate coats which also generated a standardized surface consistency. The resulting avian-perceived chromatic dissimilarity (just noticeable difference: JND) from natural robin egg colours was approximately 2 JND for the mimetic eggs [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…All models were painted a robin-like blue colour (paint-mix details sourced from [ 31 ]), in triplicate coats which also generated a standardized surface consistency. The resulting avian-perceived chromatic dissimilarity (just noticeable difference: JND) from natural robin egg colours was approximately 2 JND for the mimetic eggs [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a generalist obligate avian brood parasite, the potential for eggshell mimicry in brown‐headed cowbirds has not been thoroughly investigated using visual models predicting avian‐perceivable variation in eggshell coloration (reviewed in Hauber et al., 2020). Further, the lighting conditions under which the host compares the parasitic egg(s) to its own clutch have also not been considered in detail previously.…”
Section: Discussionmentioning
confidence: 99%
“…While the cowbird's egg may resemble those of some of its host species when viewed by the human visual system (Peer et al., 2000), current evidence suggests that the similarity between cowbird and some host eggs is the result of evolutionary processes such as phylogenetic constraint, predation, and/or incidental matching, rather than mimicry (Grim, 2005). However, to date, there has been little investigation into whether cowbird eggs are more similar to host eggs than non‐host eggs when viewed by the avian visual system (but see Hauber et al., 2020), nor whether hosts are more likely to reject parasitic eggs when their eggs appear more similar to cowbird eggs as would predicted by the “mimicry hypothesis.” In this paper, we address this by examining the degree of avian‐perceived color similarity between cowbird eggs and those of both hosts and non‐hosts, considering both the visual systems of the viewers and the lighting conditions at the nest. If mimicry is present in the cowbird‐host system, we predict that the color of cowbird eggs will be more similar to the color of host than non‐host eggs, and hosts with the greatest degree of perceived cowbird‐host egg color similarity will be the most likely to reject cowbird eggs (sensu Stoddard & Stevens, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…I used two different colors of 3D-printed, cowbird-sized, -shaped, and -weighing model eggs (sourced from www.Shapeways.com: "cow bird" egg in versatile natural plastic; for manufacture and dimension details, see Igic et al 2015): mimetic painted eggs were a robin-like blue color (paint-mix details sourced from Canniff et al 2018), whereas nonmimetic, deep-blue eggs were painted with unmixed Ultramarine Winsor & Newton Galeria Acrylic paint (London, UK; following Abolins-Abols & Hauber 2020), both in triplicate coats. The resulting avian-perceived chromatic dissimilarity (just noticeable difference: JND, reviewed in Stoddard & Hauber 2017) from natural robin egg colors was ~2 JND for the mimetic eggs (Hauber et al 2019; 1-day egg rejection rate: 6.7%) and ~19 JND for the deep-blue eggs (Hauber et al 2020b; rejection: 54%) ( Fig. 1).…”
Section: Methodsmentioning
confidence: 96%
“…Robins are robust egg rejecters: in several of our previous studies we found that the median and mode for the latency of egg rejection of (e.g., non-mimetic: beige or deep-blue model eggs) is 1 day (Croston & Hauber 2014a. Therefore, I revisited each nest 1 day after the initial treatment and assessed whether the model egg was present (accepted) or missing (rejected) (as per Hauber et al 2020b). I removed any model egg still there, and then initiated the next, randomly chosen, different treatment at the same nest.…”
Section: Methodsmentioning
confidence: 99%